Tutorial on Kelly capital growth investment strategies for long term growth with application to SWFs 1 - Ziemba, William (Henry Stewart Talks, 2014)
The two trading routes available for cash, equity and equity futures hedge funds, What you must do to win consistently, Games: favorable or unfavorable, The importance of getting the mean right, Effect of data input errors on portfolio performance, It’s the means that are the most important for investment success, Asset proportions, not practical, Log utility: Bernoulli (1738), Maximizing long run growth, What does the theory tell us about long term hedge fund trading and overbetting?, Mohnish Pabrai bet issues, Kelly betting, Soros and Buffett, Using the Sharpe ratio, Kelly and half Kelly medium time simulations, Final wealth statistics by Kelly fraction: Ziemba-Hausch (1986) model, Horse racing, Effect of transactions costs, calculation of optimal place and show Kelly bets, Expected value approximation equations